Population genomics of Bombus terrestris reveals high but unstructured genetic diversity in a potential glacial refugium - Silva, Sara E. (2020)
Ongoing climate change is expected to cause temperature rise and reduction of precipitation levels in the Mediterranean region, which might cause changes in many species’ distribution. These effects negatively impact species’ gene pools, decreasing genetic variability and adaptive potential. Here we use mitochondrial DNA and RADseq to analyse population genetic structure and genetic diversity of the bumblebee species Bombus terrestris (subspecies B. terrestris lusitanicus), in the Iberian Peninsula. While this subspecies shows a panmictic pattern of population structure across Iberia and beyond, we found differentiation between subspecies lusitanicus and subspecies africanus, likely caused by the existence of barriers to gene flow between Iberia and North Africa. Furthermore, results revealed that the Iberian Peninsula harbours a large fraction of B. terrestris intraspecific genetic variation, with the highest number of mitochondrial haplotypes found when compared to any other region in Europe studied so far, suggesting a potential glacial refugium role for the Iberian Peninsula. Our findings strengthen the idea that Iberia is a very important source of diversity for the global genetic pool of this species, as rare alleles may play a role in population resilience against human or climate-mediated changes